2010
DOI: 10.1111/j.1365-2206.2009.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of transcultural fostering

Abstract: Licensed Canadian foster parents residing in a central province where Aboriginal children have been overrepresented in child protection caseloads and Aboriginal adults under‐represented as caregivers were asked about their experiences fostering children from a different culture than their own during telephone interviews. In response to the question ‘What are the benefits of fostering children who have different values, beliefs and traditions than you?’, 48 unique responses were received. These responses were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…International evidence exists showing that being placed from one's birth family to transcultural foster care impacts the ethnic identity of foster youth (Barn, 2010;Brown et al, 2009;Schmidt et al, 2015;Tyrell et al, 2019;Waniganayake et al, 2019;White et al, 2008). These studies observed disconnection from ethnic cultural backgrounds and ethnicity losses (Barn, 2010;Brown et al, 2009;Clark, 2000;Tyrell et al, 2019;Waniganayake et al, 2019), (re)connection with ethnic minority backgrounds through birth parents and awareness of minority ethnicity because of differences in physical appearance between foster youth and their foster parents (White et al, 2008). These studies however did not focus on how foster youth might integrate both majority and minority identities into their lives.…”
Section: Ethnic Identity Fluctuations Of Transculturally Placed Foste...mentioning
confidence: 99%
See 1 more Smart Citation
“…International evidence exists showing that being placed from one's birth family to transcultural foster care impacts the ethnic identity of foster youth (Barn, 2010;Brown et al, 2009;Schmidt et al, 2015;Tyrell et al, 2019;Waniganayake et al, 2019;White et al, 2008). These studies observed disconnection from ethnic cultural backgrounds and ethnicity losses (Barn, 2010;Brown et al, 2009;Clark, 2000;Tyrell et al, 2019;Waniganayake et al, 2019), (re)connection with ethnic minority backgrounds through birth parents and awareness of minority ethnicity because of differences in physical appearance between foster youth and their foster parents (White et al, 2008). These studies however did not focus on how foster youth might integrate both majority and minority identities into their lives.…”
Section: Ethnic Identity Fluctuations Of Transculturally Placed Foste...mentioning
confidence: 99%
“…The formation of one’s ethnic identity is a dynamic process which develops through a reciprocal relationship between an individual and his or her social context (LaFromboise et al, 1993; Phinney et al, 2007). International evidence exists showing that being placed from one’s birth family to transcultural foster care impacts the ethnic identity of foster youth (Barn, 2010; Brown et al, 2009; Mitchell Dove and Powers, 2018; Schmidt et al, 2015; Tyrell et al, 2019; Waniganayake et al, 2019; White et al, 2008). These studies observed disconnection from ethnic cultural backgrounds and ethnicity losses (Barn, 2010; Brown et al, 2009; Clark, 2000; Mitchell Dove & Powers, 2018; Tyrell et al, 2019; Waniganayake et al, 2019), (re)connection with ethnic minority backgrounds through birth parents (Mitchell Dove and Powers, 2018) and awareness of minority ethnicity because of differences in physical appearance between foster youth and their foster parents (White et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although kinship care is challenging, it has been underfunded and under-resourced (Hill, 2016;Mutchler et al, 2007;Purcal et al, 2014;Worrall, 2006). Additionally, there is a shortage of Indigenous foster parents, despite there being an overrepresentation of Indigenous children in the child welfare system, which has been attributed to a mistrust of social workers and traumatic child welfare experiences (Brown et al, 2010;Halverson et al, 2002;Hanna et al, 2017). The literature suggests detrimental effects from placing Indigenous children in White foster homes, especially because children who are disconnected from their Indigenous culture and community tend to have difficulty developing a positive self-identity (Becker- Green, 2009;Moss, 2009;Sinclair, 2008).…”
Section: Children In Carementioning
confidence: 99%